2018
DOI: 10.1111/odi.12940
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐band imaging pattern classification in oral cavity

Abstract: The proposed classification could serve as a guide for clinicians approaching narrowband imaging, especially at early stages of the learning curve, to differentiate normal mucosa from malignant lesions and possibly reduce the number of unnecessary biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…A second criticism of FS is the high costs and time needed. However, as described by Di Nardo et al, an intelligent use is mandatory (Di Nardo et al, ): in our operating room, we start the operation with an NBI‐guided tattoo (Tirelli, Marcuzzo, et al, ) followed by tumour removal and FS sampling, and then, while waiting for the response (40–60 min depending on the number), we perform neck dissection so as not to waste time; moreover, we continuously work together with the pathologist to minimise sampling and reading errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second criticism of FS is the high costs and time needed. However, as described by Di Nardo et al, an intelligent use is mandatory (Di Nardo et al, ): in our operating room, we start the operation with an NBI‐guided tattoo (Tirelli, Marcuzzo, et al, ) followed by tumour removal and FS sampling, and then, while waiting for the response (40–60 min depending on the number), we perform neck dissection so as not to waste time; moreover, we continuously work together with the pathologist to minimise sampling and reading errors.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature, two different approaches to help the surgeon reduce the rate of positive margins have been proposed and validated: narrow‐band imaging (NBI) and piecemeal resection. By enhancing mucosal and submucosal vessels and the vascular pattern alterations indicative of malignant transformation (Tirelli, Marcuzzo, & Boscolo Nata, ), intraoperative NBI reduces the rate of positive superficial margins (Tirelli, Marcuzzo, et al, ; Tirelli et al, ; Tirelli, Piovesana, Gatto, Torelli, & Boscolo Nata, ; Tirelli, Piovesana, et al, ). On the other hand, piecemeal resection, introduced to allow laryngeal tumour removal through the small diameter of laryngoscopes (Steiner & Ambrosch, ), has been used in TOS for oropharyngeal (Hinni, Zarka, & Hoxworth, ) and oral cancer (Choi et al, ; Tirelli, Piovesana, et al, ) because it allows one to identify the transition from cancer to healthy tissue thereby improving deep margin control.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review [10], the four pattern system [2] is considered the most effective in oral cavity, being the all types: type I (physiological arborization of IPCL), type II (circuitous or dilated IPCL), type III (convoluted/winding and/or elongated IPCL) and type IV (complete loss of organization/annihilation of IPCL). A more recent classification has been proposed for oral cavity [11], but it cannot be taken into account as the authors do not show any statistical analysis to corroborate their results. Data from the literature have shown that oral lesions with NBI pattern III and IV have increased chances of anatomopathological diagnosis of High Grade Dysplasia (HGD), oral SCC (OSCC) and OSCC in situ (Cis), when compared to those with the NBI pattern I and II [10, 12, 13].…”
Section: Introductionmentioning
confidence: 96%
“…Despite these excellent results, routine clinical use in the inspection of oral cavity may present some difficulties. Many studies often exclude Oral Potentially Malignant Disorders (OPMDs), as they are considered confounding factors [9], especially in case of patients with Oral Lichen Planus (OLP) [911] due to the dishomogeneous/ulcerated aspect of the lesions and the correlation with high-grade NBI patterns. The site of the lesion is sometimes considered as bias too, due to different types of epithelium found in oral cavity; usually, epithelium of the oral cavity is classified into four categories, namely: lining epithelium (non-keratinized; e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation